The Influence of Al-Bahjah's Da'wah Media on Solving Society's Social Problems - Sunoto toto Sunoto (Edueksos Jurnal Pendidikan Sosial & Ekonomi, 2023)
ABSTRACTIn Cirebon Regency, there are several social problems that must be resolved, such as the number of juvenile delinquency, divorce, technology and morals. Da'wah is one of the alternatives in solving these problems which is broadcast through the media. The aim of this research was to find out the influence of Al-Bahjah’s dakwah media on solving social problems in society. Kind of this research is correlation research with a quantitative approach. The techniques to collecting the data are questionnaires with a total sample of 50 respondent, structured and unstructed interviews and observations in the object of research. The techniques of data analysis are simple regression, hyphotesis tes (t test) and determination test. The result of this research indicate that: (1) based on signification test obtained results where the variable of dakwah media with a significance value of 0,000 < 0,05 with tcount of 4,430 > Ttable 2,010. It means that there is a significant influence between media of dakwah and resolution of social problems. Based on the facts on the ground too, da'wah through technological media has an effect on efforts to provide Islamic solutions to various life problems and move people from a better situation. Although there are some people who feel that their social problems have not been fully resolved through the existence of the da'wah media.Keywords: Da'wah, Social Issues, Media